Role of ACTN3 Gene rs1815739 Polymorphism and Its Effects on Mandibular Morphogenesis - George, Ashwin Mathew; Priyadharsini, Jayaseelan Vijayashree; Felicita, Sumathi; Sundari, Shantha; Subramanian, Aravind Kumar (Orthodontics & craniofacial research, 2025)
ABSTRACT Objectives Genetic polymorphism of the α‐actinin‐3 (ACTN3) gene has an influence on the facial skeletal profile, with the activity of the α‐actinins protein influencing the contractile properties of the masseteric muscles. This study examines the association between the ACTN3 rs1815739 polymorphism through a Stop Codon (changing 577RR to 577XX) resulting in variations in mandibular morphogenesis. Materials and Methods Two hundred and fifty subjects were categorised into three groups. The control group (Group 1) comprised 100 patients with skeletal Class I malocclusion. The experimental group (Group 2) had 150 subjects with skeletal Class II malocclusions and a retrognathic mandible, divided into two groups of 75 subjects each based on the ramal heights (short ramal height‐Group 2a) and (long ramal height‐Group 2b). Saliva samples of the subjects were analysed to identify the genotype of the rs1815739. Tissue samples were taken to quantify the mRNA expression in the different alleles studied. Results Polymorphism of the ACTN3 gene with risk homozygous TT genotype was linked only to subjects with short ramal height. The highly variable polymorphic site exhibited a substitution of the ancestral allele cytosine (C) with thymine (T) inhibiting protein synthesis. The mRNA expression was also found to be reduced (p < 0.05) in the short ramal height group. Conclusion ACTN3 577XX polymorphism is more common among individuals with skeletal Class II malocclusion and short ramal height in the Dravidian population. It results in decreased protein expression in the masseteric muscle, which contributes to variations in sagittal and vertical facial dimensions.